Malaysian Prefabricated Housing; The Real Causes of Fragmentation Issues and Steps to Overcome - Ahmad, Abd Jalil; Fadhilah, Binti Md Fazil; Chong Wan, Siang; Mohd Amir Shazwan, Hashim (IOP Publishing, 2023)
Many prefabricated housing projects in develop countries have proven their success, and since 1960s Malaysia has taken great steps towards applying this concept. Housing is suitable for prefabricated due to its repetitious of design, simultaneous construction, large scale and impact to environment. Unlike develop countries that far advanced, Malaysia still face critical issues including on fragmentation. Fragmentation is defined as working in isolation, work in separation and division that happens among different parties in the same project. Various research on prefabricated housing has been conducted focusing on supply chain, modularization, automation, design, payment and procurement but lack focus on fragmentation. This paper will investigate the real causes of fragmentation issues in Malaysian prefabricated housing, their consequences and suggest steps to overcome. The methodology used is mix method with 118 questionnaires were analyzed using SPSS and combine with deep interviews with respondents from prefabricated manufacturers, prefabricated installers, academicians, consultants, developers, main contractors and M&E contractors, through targeted sampling technique. The result shows the causes of fragmentation are unfamiliar with prefabricated concept, late involvement of prefabricated companies and the practice of segregation culture while the steps to overcome are by establishing close integration since beginning, each party is appointed early and direct contract between prefabricated companies and developers. This research has contributed to the body of knowledge by detailing the real causes that make fragmentation issue become critical and suggest steps to overcome them and both had been verified by respondents who are expert, experienced and represent all the stakeholders involved in prefabricated housing.